Benjamin Franklin's printing network : disseminating virtue in early America - Frasca, Ralph, 1962- (University of Missouri Press, 2006)
"Explores Benjamin Franklin's network of partnerships and business relationships with printers. His network altered practices in both European and American colonial printing trades by providing capital and political influence to set up working partnerships with James Parker, Francis Childs, Benjamin Mecom, Benjamin Franklin Bache, David Hall, Anthony Armbruster, and others"--Provided by publisher